A visual clone analysis method - Navas-Su, Jose; Gonzalez-Torres, Antonio; Hernandez-Castro, Franklin (Frontiers in Computer Science, 2025)
The process of creating high-quality software is always a significant challenge for developers. Besides acquiring and honing the trained skills and knowledge needed to fulfill this process successfully, they face the persistent need for better methods and tools to understand and analyze software systems. This research proposes a method for building metrics-based visual analytic tools fully integrated into the development environment to enhance the capabilities and convenience of these working environments. In particular, duplicate code metrics allow developers to locate and correct potential threats to software quality, understandability, maintainability, and scalability. Refactoring duplicate code should help avoid duplication of effort during maintenance and decrease the possibility of introducing errors and inconsistencies. The proposed approach is demonstrated by programming a plugin component that detects and allows the visual analysis of duplicate code in a working project. We developed this tool for a well-known integrated development environment.